Empirical assessment of sustainability and feasibility of government debt: The Philippines case - Duo Qin; Marie Anne Cagas; Geoffrey Ducanes; Nedelyn Magtibay-Ramos (Queen Mary University of London, Department of Economics, 2005)
This paper develops empirical methods of assessing the sustainability and feasibility of public debt using the No Ponzi Game criterion, using the Philippines as the testing case. Both historical data and forecasts generated by a quarterly macro-econometric model are used in the assessment. Stochastic simulations are carried out to mimic future uncertainty. The test results show that, up to the end of the present administration in 2010, the Philippine government debt is not sustainable but weakly feasible, that the feasibility is vulnerable to major adverse shocks, and that simple budgetary deficit control policy is inadequate for achieving debt sustainability or strengthening feasibility.
Keywords: H62; H63; E62; F34; C53; 330; Government debt; Ponzi game; Rollover bond portfolio; Öffentlicher Haushalt; Öffentliche Schulden; Haushaltskonsolidierung; Empirische Methode; Philippinen